Challenges in the conservation and management of legal reserve areas in Brazilian grassland and savanna ecosystems in the face of global climate change - Tomas, Walfrido Moraes; Baggio, Rodrigo; Berlinck, Christian Niel; Camilo, André Restel; Cunha, Catia Nunes da; Damasceno-Junior, Geraldo; Durigan, Giselda; Dutra-Silva, Rodrigo; Fidelis, Alessandra; Garcia, Letícia Couto; Herrera, Heitor Miraglia; Libonati, Renata; et al. (Pesquisa Agropecuaria Brasileira, 2024)
Legal reserve areas (LRAs) are a fundamental part of the Brazilian conservation strategy, together with permanent preservation areas. The LRAs are intended to maintain biodiversity and can be managed sustainably. When these areas are home to ecosystems that depend on fire and grazing, such as native grasslands and savannas, management practices that are suitable for their conservation and for dealing with the effects of global climate change should be adopted. However, this subject is still poorly discussed in Brazil, and public policies are not clear on this matter. This review article describes the grassland and savanna ecosystems in Brazil, the legal aspects related to the management of LRAs, the current and future climate scenarios, and the relationship between climate and fire risk. It also presents a review about the use of fire and grazing in grassland and savanna ecosystems, the legal challenges related to their application in LRAs, and the use of geotechnologies to monitor these practices. The conclusion is that grazing and fire, as management tools, are adequate for LRA functions, as long as they are practiced in accordance with legal and scientifically based standards to avoid the negative effects of their incorrect use.